Amino acids and athletic performance: A mini conference in Oxford - Stewart, A. M. (Sportscience, 1999)
Summary of the mini-conference: Supplementing with glutamine reduces the risk of infections, and supplementing with branched chain amino acids benefits physical and mental performance in long endurance events, according to presenters at this one-day conference. One speaker argued that creatine supplementation was not ergogenic in competitions. A panel suggested renaming overtraining as the underperformance syndrome, but some members of the audience preferred underrecovery.